Case Report: Rare Acute Abdomen: Focal Nodular Hyperplasia With Spontaneous Rupture - Si, Ying; Sun, Bo; Zhao, Ting; Xiao, Ke; Zhao, Dong-Xia; Huang, Yong-Mao (Frontiers in Oncology, 2022)
Focal nodular hyperplasia (FNH) of the liver is a benign lesion characterized by hypertrophic nodules with central star-shaped fibrous scars. The etiology and pathogenesis of FNH are not completely understood. A 43-year-old man was hospitalized because of acute abdominal pain. Emergency computed tomography(CT) showed hepatic tumor rupture and bleeding. The patient’s condition improved following arteriographic embolization to stop bleeding. Laparotomy confirmed spontaneous rupture and hemorrhage of focal hyperplasia and the patient remains asymptomatic after an uneventful recovery. FNH with spontaneous rupture and bleeding is extremely rare. Currently, there is no unified management standard for FNH and most previous studies recommend observation and follow-up. We recommend consideration of surgical treatment of cases with spontaneous rupture and bleeding.